DIGITAL TECHNOLOGIES FOR COMPLETE DENTURES REALIZATION - Diana Diaconu-Popa; Anca Vițalariu; Monica Tatarciuc (Romanian Dental Association for Education, 2020)
Full dentures are not technologically difficult to make, but involve a large number of clinical and technological steps, which can lead to an increased risk of errors. With the development of digital technologies, subtractive and additive methods, the working flow was considerably reduced and the precision of the prosthetic devices was greatly increased. These technologies use industrially produced materials, with physical, chemical and mechanical properties superior to the conventional materials. The main motivations for accepting or rejecting a new technology include the relative advantages they offer compared to the classical methods, and these can be represented by time saving, financial advantages, and clinical benefits. The present study aims to analyze the advantages and disadvantages of complete denture made by digital methods.